PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KREATIF DITINJAU DARI SELF EFFICACY SISWA SMP - Siti Mashfiyatur Rohmah (Universitas Muhammadiyah Surabaya, 2024)
An effect of the project-based learning model on creative thinking ability is reviewed from the self-efficacy of junior high school students. This research aims to describe the influence of project-based learning on creative thinking ability as reviewed from Self Efficacy. The research method used an experimental research method with a quantitative approach. The research design used a nonequivalent control group design with research samples, namely students in grades VII-I and VII-J at SMP Negeri 17 Surabaya who were selected using the purposive sampling technique. The data on self- efficacy and creative products were obtained by using the self-efficacy scale and the creative product assessment rubric which were analyzed descriptively. The data on creative thinking ability were obtained using pretest and posttest values which were analyzed by the Independent Sample t-test at a significance level of 5%. The results showed that α = 0,005 project-based learning had a significant effect on the creative thinking ability of junior high school students as reviewed from self-efficacy.